Community empowerment through child-friendly village program in Bedahlawak Village, Jombang Regency - Erwin Dwi Kurnia,; Eunike Emmanuela.B,; Fadilah Dewi Anggun Permatasari,; Mega Dewi Ambarwati,; Sultoni Fikri, (Technium Social Sciences Journal, 2022)
In the current era of globalization, there is access to technology that offers convenience, as well as its sophistication at this time. The existence of advances in the field of technology makes people often prefer to use advanced technology in the form of mobile phones or Cellphones in their daily lives. For example, in reading news through online media, watching news through digital platforms, they often use mobile phones instead of watching on television or reading in newspapers. This can lead to a new habit that is fond of operating mobile phones. That things like that will quickly and easily be imitated by their children. It is not uncommon to find that many parents often give mobile phones to their children to calm their crying child. Especially with the COVID-19 Pandemic, which requires people to work and study from home. Of course this will make the use of mobile phones more frequent, if things like this are done continuously it will become a bad habit if the role parents doesn't limit use of Cellphones or cell phones for children. With the frequent use or operation of mobile phones among children, what is feared is that they are dependent on mobile phones. The use of mobile phones will have good results if used in accordance with their functions and needs and will have bad consequences if the mobile phone has become a habit for children, from those who like to play outside house to often lock themselves in the room by only playing mobile phones or technological tools other sophisticated.